A new species of Dixonius Bauer, Good, and Branch, 1997 (Squamata: Gekkonidae) ranging through the Cardamon Mountains of Cambodia to the southern Mekong Delta of Vietnam - Grismer, L. Lee; Neang, Thy; Tri, Ngo Van; Grismer, Jesse L. (Zootaxa, 2025)
A new species of the gekkonid genus Dixonius from the Cardamom Mountains of southern Cambodia and the southwestern Mekong Delta region of Vietnam is delimited based on a molecular phylogeny comprised of 1,396 base pairs of the mitochondrial gene ND2 and diagnosed by statistically significant size-corrected morphometric, meristic, and color pattern characteristics. The new species, D. luuhoangorum sp. nov., is the sister species of D. sambhupura from approximately 200 km to the northwest in Kratie Province, eastern Cambodia. The highly fragmented topography through which this species ranges is mirrored by its peculiar phylogeographic relationships where some of the geographically proximate northern Cardamom Mountain populations are more closely related to the Mekong Delta populations of southwestern Vietnam. The description of D. luuhoangorum sp. nov. continues to underscore the localized endemism within this genus and the necessity for continued systematic based fieldwork in both well-explored and under-explored regions of Indochina in order to establish conservation measures.